2007
DOI: 10.1364/oe.15.000955
|View full text |Cite
|
Sign up to set email alerts
|

Harmonically mode-locked VECSELs for multi-GHz pulse train generation

Abstract: We report on optically-pumped vertical-external-cavity surface-emitting lasers passively mode-locked with a semiconductor saturable-absorber mirror. The potential of harmonic mode-locking in producing pulse trains at multigigahertz repetition rates has been explored. The results present first systematic study of multiple pulse formation in passively mode-locked VECSELs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…The physical mechanisms for the spectral shifts in SDLs are discussed in [12]. Similar spectral blue-shifting has been reported for the harmonically mode-locked SDL [13].…”
Section: Resultssupporting
confidence: 60%
“…The physical mechanisms for the spectral shifts in SDLs are discussed in [12]. Similar spectral blue-shifting has been reported for the harmonically mode-locked SDL [13].…”
Section: Resultssupporting
confidence: 60%
“…If the separation between the pulses becomes longer, two or more pulses have a gain advantage, which introduces modelocking instabilities or harmonic modelocking. The harmonic modelocking regime was studied in detail in [26]. The authors confirmed that strong saturation and fast recovery of the gain causes harmonic modelocking, and that the pump power has a strong effect on the pulse break up.…”
Section: Introductionmentioning
confidence: 88%
“…For DPSSLs, longer cavities and therefore lower pulse repetition rates enabled pulse energies above 10 µJ at a few MHz repetition rate and peak powers in the Megawatt regime directly from SESAM modelocked DPSSLs without further amplification [22][23][24]. So far, the lowest repetition rate of SESAM modelocked VECSELs is around 340 MHz [25,26] with no more than 15 mW average output power. The pulse energy was limited to a few nJ even for Watt-level average output powers.…”
Section: Introductionmentioning
confidence: 99%
“…Harmonic mode-locking has already been demonstrated in VECSELs, both in a coupled cavity configuration 13 and as a result of gain saturation the laser, 14 but the repetition rates achieved did not exceed 10 GHz. Here, we present a VEC-SEL emitting pulses as short as 1.1 ps at repetition rates up to 147 GHz via passive harmonic mode-locking in a coupled cavity configuration.…”
mentioning
confidence: 97%